Optimization of real work lectures as an actualization of community service activities at UIN Sunan Kalijaga - Maragustam, Maragustam; Khodijah , Siti; Rohmi, Puspo (At-Tajdid: Jurnal Ilmu Tarbiyah, 2024)
The research questions here are (1) How effective is the competency-based implementation of PLP-KKN Integrative FITK UIN Sunan Kalijaga? (2) What is the pattern of PLP-KKN Integrative at the faculty level within UIN Sunan Kalijaga, specifically FITK? This study employs a qualitative-phenomenological approach; respondents are selected using purposive and snowball sampling; data collection techniques include observation, documentation, observation, and focus group discussion (FGD). Data analysis techniques utilize Miles and Huberman’s method, which includes collection, presentation, reduction, and verification and conclusion of data. The findings indicate that (1) the integration of PLP and KKN, known as PLP-KKN Integrative FITK, is less effective from the perspective of competency achievement, (2) the pattern of PLP-KKN Integrative FITK or Pengenalan Lapangan Profil Lulusan (PLPL) program at UIN Sunan Kalijaga is separated; PLP or PLPL separately and KKN separately. Specifically for KKN, FITK students are integrated with UIN Sunan Kalijaga’s KKN as a demand for competencies and core values of UIN Sunan Kalijaga, namely integration-interconnection.